Interpretive Structural Modeling of Factors Affecting Organizational Ambidexterity in the Ministry of Sports and Youth - Ainolah Ahmadnejad Joghie; Mozafar Yektayar; Mozhgan Khodamoradpoor (Research in Sport Management and Marketing)
Purpose: The goal of this study was to present an interpretive structural modeling of factors affecting organizational ambidexterity in the Ministry of Sports and Youth.Methods: The research methodology was mixed method and the plan was exploratory. The statistical population of this study consisted of experts who were selected purposefully based on theoretical saturation of 15 of them. Semi-structured interviews were used to collect data in the qualitative study and a questionnaire was used to collect data in the quantitative study. In order to evaluate the quality and validity of the findings, validation, transfer, reliability and verification, and for analyzing qualitative study data, coding and quantitative study of interpretive structural modeling (ISM) and software ISM software were used.Results: As a result of qualitative data analysis, 14 factors affecting organizational ambidexterity were identified and as a result of quantitative data analysis these factors were classified into five levels, and in the meantime, organizational culture, job characteristics and organizational capabilities were in the most rich layer, Conclusion: This shows that cultural, organizational and job capacities needed for this phenomenon to move in the complex path of organizational dualism at the beginning.